Analysis of Chlorophyll-A Content and Water Quality of Ciwaka Reservoir, Serang Banten - Lail, Sakhirotul; KN, Aditya Rahman; Khastini, Rida Oktorida (Metamorfosa: Journal of Biological Sciences, 2022)
The research was conducted to determine the quality of the waters of the Ciwaka Reservoir, Serang City, Banten, based on the content of chlorophyll-a and the presence of phytoplankton. The relationship between the chlorophyll-a content and the presence of phytoplankton with the physical-chemical parameters of the waters was also being analyzed. Thus the results from the study were used as content for learning media education research. This research was conducted from February-July 2021, in Ciwaka Reservoir, Serang City, Banten. A sampling of water at three stations was carried out using the purposive sampling method. Chlorophyll-a analysis was carried out using spectrophotometric methods. The results of chlorophyll-a analyze in each station ranged from 7,458 g/L – 34,352 g/L. Ciwaka Reservoir is included in the category of waters that are eutrophic (polluted) due to high nutrient levels. The water quality of Ciwaka Reservoir is still in good condition according to the designation of class 2 water quality standards in PP No. 82 of 2001. The content of chlorophyll-a and the presence of phytoplankton (abundance, diversity, and dominance) only has a weakness with the brightness (r = 0.000). Phytoplankton diversity was strongly correlated with temperature (r = 0.994). Phytoplankton dominance was strongly related to DO (r = 0.998) and BOD (r = 0.998). Keyword: E utrophic , C hlorophyll-a , Ciwaka Reservoir